Synthesis of new thioester derivative of aspirin and study its effect on some biochemical parameters in blood serum of rabbits - Zaid Abdalkader Dawood; Firas Shawqi Algburi; Nazar Ahmad Naji (Tikrit Journal of Pure Science)
This presented work was included synthesis of new thioester derivatives by reaction of Aspirin (a non-steroidal anti-inflammatory drugs) (NSAIDs) and Captopril as a carrier which is used as an antihypertensive drug and an inhibitor for angiotensin-converting enzyme (ACE). Aspirin was converted into acid chloride of aspirin then reacted with SH group of captopril to afforded of 1-(3-((2-acetoxybenzoyl)thio)-2-methylpropanoyl)pyrrolidine-2-carboxylic acid and characterized by FT-IR and 1HNMR spectroscopy. The effect of synthesized compound was studied on some biochemical parameters in the blood serum of rabbits. Results of this study indicated: significant increase in the level of total fucose, total protein and globulin.   Non- significant increase in the level of albumin, creatinine, glutathione and uric acid, significant decrease in level of Triglycerides and non-significant decrease in the level of Cholesterol, and malondialdehyde.